2016
DOI: 10.1111/ggi.12935
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of physical prefrailty among Japanese healthy older adults

Abstract: These results suggest that the appearance of autonomic failure, oral malfunction and some psychological factors in relation to depressed mood, but not anthropometric measurements, are characteristic of prefrailty. Geriatr Gerontol Int 2017; 17: 1568-1574.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The Japanese version of the Cardiovascular Health Study (J‐CHS) is the most widely used model for evaluations of frailty To date, various simplifications and modifications of this model have been developed . We used the J‐CHS, which was validated for the evaluation of frailty . The J‐CHS includes the following items: (i) Have you lost ≥2 kg during the past 6 months?…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese version of the Cardiovascular Health Study (J‐CHS) is the most widely used model for evaluations of frailty To date, various simplifications and modifications of this model have been developed . We used the J‐CHS, which was validated for the evaluation of frailty . The J‐CHS includes the following items: (i) Have you lost ≥2 kg during the past 6 months?…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review of risk factors for malnutrition in older adults, frailty and constipation were significant risk factors for malnutrition ( 19 ). Matsushita et al reported that, in the logistic regression model for the prevalence of prefrailty, chronic constipation was a significant and independent determinant, and they suggested that autonomic failure is associated with prefrailty among older individuals ( 20 ). According to a study that investigated the frailty status of inpatients >65 years old in Shanghai, constipation is a risk factor of frailty, and it was recommended to include frailty as an indicator in the existing assessment to rate the disease and develop a disease observation plan ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…All participants provided written consent for inclusion in the study. Other cross-sectional and longitudinal results have been published elsewhere [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%